Kepentingan Kaunseling dalam Menangani Masalah Rumahtangga - Md. Yusoff, Yusmini (Jurnal Usuluddin, 2003)
This article tries to elaborate the importance of counselling as a method in handling marital and family problems. It includes three significant counselling stages in marriage setting such as pre-marital, marital and family counselling. Family crisis and the function of counselling are also described.